Cooling thermal parameters, microstructure, segregation and hardness in directionally solidified Al–Sn-(Si;Cu) alloys. (5th May 2015) - Bertelli, Felipe; Brito, Crystopher; Ferreira, Ivaldo L.; Reinhart, Guillaume; Nguyen-Thi, Henri; Mangelinck-Noël, Nathalie; Cheung, Noé; Garcia, Amauri
Graphical abstract: Highlights: Experimental dendritic growth laws are proposed for solidification of Al–Sn-(Cu;Si) alloys. The Sn distribution is characterized by inverse macrosegregation profiles. Hall–Petch type equations are proposed relating the primary dendritic arm spacing to hardness. Abstract: The morphology and length scale of the phases forming the microstructure of sliding bearing alloys are known to affect wear, mechanical and corrosion resistances. Al–Sn alloys have good anti-frictional properties due to the presence of Sn. However, with the current trends in engine design, these alloys are not able to support the demanded heavy loads. An alternative way to reach this requirement can be the alloying with third elements such as Si and Cu. Despite the importance of their application properties, studies on the development of microstructures of these multicomponent alloys are rare in the literature. In the present investigation Al–Sn-(Cu;Si) alloys were directionally solidified (DS) under transient heat flow conditions, and a thorough characterization is performed including experimental growth rates and cooling rates, segregation, optical and scanning electron microscopies and primary dendrite arm spacings, λ 1 . Experimental growth laws are proposed relating the dendritic spacing to solidification thermal parameters. Furthermore, the scale of the dendritic morphology, the distribution of second phases in interdendritic regions and the macrosegregation pattern are shown to affect the hardness along the length of the DS castings. Hall–Petch type equations are proposed relating hardness to λ 1 .